Changeability why some companies are ready for change - and others aren?t - Jarrett, Michael (Harlow Financial Times, 2009)
Are you falling behind your competitors? Are you too slow getting your products to market? Are your overheads too high? These are just some of the challenges that companies face. However, initiating successful change strategies is far from easy. 70% of all change programmes fail. This book shows how you can make sure that when change happens (and it frequently does) your company is ready for it.
Includes bibliographical references and index.
Keywords: Organizational change